Tunable magnetocrystalline anisotropy of two-dimensional Fe3GeTe2 with adsorbed 5d-transition metal. Issue 35 (1st September 2022) - Yuan, Miaojia; Tan, Ruishan; Li, Mengmeng; Jin, Cui; Jing, Tao; Sun, Qilong
Abstract : We demonstrate the manipulation of magnetic property and magnetocrystalline anisotropy energy in layered Fe3 GeTe2 via the surface adsorption of W atom and applied biaxial strain. Abstract : The demand for ultra-compact spintronic devices with lower energy consumption and higher storage density requires two-dimensional (2D) magnetic materials with tunable magnetocrystalline anisotropy (MCA) energy. Employing first-principles calculations, we have investigated the influence of W atom adsorption and biaxial strain on the magnetic properties of layered Fe3 GeTe2 . We demonstrate that the adsorption mode and applied strain play a critical role in determining their MCA. The Fe3 GeTe2 adsorbed with W atoms undergoes a change in spin reorientation from out-of-plane to in-plane magnetization, yielding a colossal MCA up to −13.112 erg cm −2 . The dominant contribution to these unexpected changes mainly arises from the W atoms with emerged magnetism and large SOC. Moreover, our results reveal distinct strain-driven modulation behaviors of the MCA in different adsorption configurations. The underlying atomistic mechanism mainly involves the alteration of various W-derived 5d-orbital states under the strain effect, leading to competitive changes of the corresponding spin–orbit coupling energies between the spin-parallel and spin-flip channels. Our findings not only provide useful guidance in optimizing the MCA performance of 2D magnetic crystals but also highlight the potential of W-adsorbed Fe3 GeTe2 in the applications of new-generation magnetic memory storage devices.